Identification of key performance parameters during off-spin bowling with a smart cricket ball - Fuss, F. K.; Lythgo, N.; Smith, R. M.; Benson, A. C.; Gordon, B. (Sports Technology, 2011)
A smart cricket ball, instrumented with three high-speed MEMS gyroscopes, was used to measure performance parameters during off-spin bowling. The average spin rate and finger torque generated by the bowler were 22.7 rps and 0.28 N·m, respectively. The arm motion could be clearly identified on the spin-axis vector diagram. The spin-axis vector described a loop that closely followed the orientation of the bowler's forearm. The centre of pressure (COP) of the finger force was located between the ring and the middle finger. A set of performance parameters was identified in this study that can be used to quantify off-spin bowling performance in the future. These performance parameters are: the spin rate of the ball, the position of the spin axis with respect to the plane of the seam, the amount of torque applied to the ball by the bowler, the bowler's angular arm velocity, the finger's COP (where the force is applied to the ball) and the impact point on the ball.